„Išlaisvinti“, pasmerkti ir „nedėkingi“: Ukrainos ir ukrainiečių bolševikinė „resovietizacija“ (1943 m.–6 deš. pradžia) - Stiazhkina, Olena (Genocidas ir rezistencija, 2023)
The purpose of this article is to analyse the first steps of “liberation” and restoration of the pre-war status quo for the Bolshevik government in Ukraine. The task is to find out what practices of “liberation” the people experienced under the Soviet occupation; in what way did the Bolsheviks react to the revitalization of the national idea; how re-Sovietization became the foundation for the restoration of the Russian imperial order; how Ukraine became a kind of a bridgehead for reinventing the model of Soviet imperialism in its “Russo-centric” posture. In this text, re-Sovietization will be considered as the mechanisms and practices (together with the tools) of the Bolshevik government in relation to Ukrainian communities that came out of the war with intentions of public solidarity and the ability to resist, dangerous for the Kremlin. The source base of the work includes archival documents of central authorities, security services, memoirs, statistical data, and correspondence. The methodological basis is the concept of agency, which implies the ability to choose options for people’s own life under any circumstances. Conclusions: right at the first stages of returning to Ukrainian lands, the Bolsheviks resumed the repressive and marauding practices that were widespread before the World War II. Through condemnation and repressive policy, a blow was struck on the Ukrainian national revival. Due to broad campaigns against “Ukrainian bourgeois nationalism” and for “gratitude to the Russian people for liberation”, Ukrainians were “pushed aside” both as victims and as heroes of the World War II.